2011
DOI: 10.1016/j.homp.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of repeated olfactory administration of homeopathic Sulphur or Pulsatilla on electroencephalographic alpha power in healthy young adults

Abstract: Introduction Homeopathic pathogenetic trials usually rely on symptom self report measures. Adding objective biomarkers could enhance detection of subtle initial remedy effects. The present feasibility study examined electroencephalographic (EEG) effects of repeated olfactory administration of two polycrest remedies. Methods College student volunteers (ages 18–30, both sexes) from an introductory psychology course were screened for good health and relatively elevated Sulphur OR Pulsatilla symptom scores on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…An additional aspect of the larger study involved evaluation of within-session transient EEG a-band effects from different numbers of succussions (stirred, 20, 40, or 100 succussions) performed on the verum and placebo sniff dilutions (detailed methods on succussion levels and sniff test results have been reported elsewhere). 48 The contents were one of two well-documented, widely used homeopathic remedies, Sulphur (mineral) or Pulsatilla (plant), and associated control solvents (water or a water-ethanol mixture). The order of the dilutions used in a session was randomized, using computer-generated sequences over the 3 weeks for each subject.…”
Section: Bell Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…An additional aspect of the larger study involved evaluation of within-session transient EEG a-band effects from different numbers of succussions (stirred, 20, 40, or 100 succussions) performed on the verum and placebo sniff dilutions (detailed methods on succussion levels and sniff test results have been reported elsewhere). 48 The contents were one of two well-documented, widely used homeopathic remedies, Sulphur (mineral) or Pulsatilla (plant), and associated control solvents (water or a water-ethanol mixture). The order of the dilutions used in a session was randomized, using computer-generated sequences over the 3 weeks for each subject.…”
Section: Bell Et Almentioning
confidence: 99%
“…Results of the placebo-controlled olfactory activation component of the larger study that examined specific transient relative EEG a-effects from 2-second sniffs of remedy and placebos at different succussion levels were reported elsewhere in detail. 48,* The data analysis and current article focus only on the pre-and postresting EEG segments as functions of time (week 1, 2, 3) and dilution (6c, 12c, 30c).…”
Section: Bell Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Neurophysiological assessments enable utilization of more objective and sensitive tools than crude behavioral observations or self-report scales for assessing the real-time dynamics of an organism at integrative levels of functioning such as the central nervous system. 19,43 In animal research, for example, Ruiz-Vega et al 44 showed that homeopathically prepared medicines such as Coffea cruda at 30c potencies can produce increases in the electroencephalographic delta band power of slow wave sleep (stages 3 and 4) versus placebo.…”
Section: Introductionmentioning
confidence: 99%
“…8,56 The secondary hypothesis, based on homeopathic theory 20,42,57 and accumulating basic science data on nanoparticles and succussion-related unique alterations in the dynamic structure of the ethanol-water solvent networks of specific remedies, 5869 was that Coffea cruda and Nux vomica would differ from one another in the pattern of their nonlinear EEG effects. Skeptics would argue the null hypothesis, given the 30c doses (potencies) used of both medicines would have been diluted past Avogadro's number and would, from a diluted bulk form source molecule perspective, contain no active ingredients and hence, effects no different from placebo.…”
Section: Introductionmentioning
confidence: 99%